Text-Based Research and Teaching : A Social Semiotic Perspective on Language in Use - Mickan, Peter; Lopez, Elise (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book illustrates the many methods available for researching language in context and for the analysis of everyday text types. Each chapter highlights language as a resource for the expression of meanings-a social semiotic resource. Text analysis is used to reveal our capacity to formulate multiple meanings for participation in different social practices-in relationships, in work, in education and in leisure. The approach is applied in text-based teaching and in the critical analysis of public discourses. The texts come from different social spheres including banking, language classes, senate hearings, national tests and textbooks, and interior architecture. Text-based research makes a major contribution to Critical Discourse Analysis. The editors and authors of this book demonstrate the value of text analysis for awareness of the role of language for accountable citizenship and for teaching and learning. This book will be of interest to anyone researching in the fields of language learning and teaching, functional linguistics, multimodality, social semiotics, systemic functional linguistics, text-based teaching, and genre analysis, as well as literacy teachers and undergraduate and postgraduate students of linguistics, media and education.
Keywords: Linguistics.; Semantics.; Sociolinguistics.; Discourse analysis.; Semiotics.; Language and languages -- Study and teaching.; elektronické knihy; electronic books